Simulation study of monoclonal antibody production using superpro, upstream process - Mohd Shamsul, Husin (2009)
The purpose of this study is to approximate hybridoma growth kinetic model by comparing simulation result from SuperPro Designer® and experimental result. Modeling of hybridoma include calculation of mass for 1 cell and its density. Two kinetic models tested in this study; experimental correlation and de Tremblay et al. (1992). Simplification need to be made as this will allow selected model to be used in SPD. Value of μmax, KsGLN, KsGLC are 1.09 d-1 (0.05 h-1), 0.3 mM (43.85 mg/L) and 0.1 mM (18.02 mg/L) respectively for de Tremblay and for experimental correlation, their values are 0.158 h-1, 0.0016 mM (0.23 mg/L) and 12.05 mM (2170.93 mg/L) respectively. Experimental data shows no stationary phase but simulation results show stationary phase. From simulation, cell count of 195907.7 while final concentration of glucose, glutamine, ammonia and lactate are 16.38, 4.07, 3.01 and 5.59 mmol/L respectively (experimental correlation) and cell count of 196185.73 while final concentration of glucose, glutamine, ammonia and lactate are 10.73, 2.09, 6.07 and 11.30 mmol/L respectively (de Tremblay). Serious deviations occurred because of simplification on de Tremblay model and inaccurate prediction of glutamine effect on hybridoma’s growth. Metabolic reaction used without taking hybridoma real behavior into account. Simulation shows exponential phase without having going through lag phase.